Bacteriocin production and inhibition of Bacillus subtilis by Lactobacillus paracasei HD1.7 in an indirect coculture system. Issue 7 (1st August 2022) - Ren, Yanxin; Zhang, Yan; Li, Xinglin; Gao, Dongni; Sun, Yanyang; Ping, Wenxiang; Ge, Jingping
Abstract: A broad-spectrum antimicrobial peptide named Paracin 1.7 was produced by Lactobacillus paracasei HD1.7, which was isolated from Chinese sauerkraut juice. In this study, the influence of cocultivation on the communication mechanism of L. paracasei HD1.7 and Bacillus subtilis was investigated. The two bacterial strains were grown in monoculture and indirect coculture, and the growth of both bacteria and bacteriocin production as well as the transcriptional level of luxS in L. paracasei HD1.7 and spo0A in B. subtilis were monitored. Bacteriocin production and cell numbers were increased significantly when L. paracasei HD1.7 cells were indirectly cocultured with B. subtilis, and bacteriocin-producing L. paracasei HD1.7 can prevent the growth and sporulation of B. subtilis . After indirect coculture with B. subtilis, the expression of luxS in L. paracasei HD1.7 increased in the exponential growth phase and decreased in the stationary phase compared to monoculture. The expression of spo0A in B. subtilis dropped in the indirect coculture compared to the monoculture. It indicate that the upregulation of luxS is due to a response to a secreted compound produced by B. subtilis . The results show L. paracasei HD1.7 has an amensalism on B. subtilis, while B. subtilis has a commensalism on L. paracasei HD1.7.